Neuropraxia following Nonsurgical Removal of Impacted Third Molar - Syed, Kamran Bokhari; Mustafa, Abdelbagi; Baig, Fawaz; Basheer, Sulphi Abdul; Elnager, Mutassim (Journal of Orofacial Research, 1970)
Extraction of mandibular third molar teeth are frequently associated with complications. The nature of the complication depends on the age of patient, extent of surgery, expertise of the surgeon and the anatomy of the neurovascular bundle surrounding the tooth. Paresthesia is an one such unpleasant complication which is not only related to functional sensory loss in the region innervated by the nerve but also having a psychosocial impact on the patient. This case report tends tohighlight a neuropraxic injury following nonsurgical extraction of a mandibular third molar and return of sensory response following neuropraxic injury.